Unexpected Copper-Catalyzed Cascade Synthesis of Quinazoline Derivatives - Chen, Zhongyan; Chen, Jiuxi; Liu, Miaochang; Ding, Jinchang; Gao, Wenxia; Huang, Xiaobo; Wu, Huayue (Journal of organic chemistry, 2013)
The first example of a copper-catalyzed cascade reaction of (2-aminophenyl)methanols with aldehydes using the combination of cerium nitrate hexahydrate and ammonium chloride has been developed, leading to a wide range of 2-substituted quinazolines in moderate to excellent yields. The efficiency of this transformation was demonstrated by compatibility with a wide range of functional groups. Thus, the method represents a convenient and practical strategy for synthesis of 2-substituted quinazoline derivatives.